A Study to Evaluate the Role of High-Resolution Computed Tomography of Temporal Bone in Pre-Operative Assessment of Ossicular Chain Status in Chronic Otitis Media (GAIMS Journal of Medical Sciences, 2026)
IntroductionChronic otitis media (COM) is a prevalent condition that can lead to ossicular chain damage and hearing loss. High-resolution CT (HRCT) scans play a crucial role in assessing the extent of disease and ossicular chain status. This study aimed to evaluate the role of HRCT temporal bone in preoperative assessment of ossicular chain status in COM patients.MethodsThis prospective observational study included 62 patients with COM who underwent HRCT temporomastoid scans. After applying inclusion and exclusion criteria, 47 patients were analyzed. HRCT scans were evaluated for malleus, incus, and stapes erosion. Surgical interventions were planned based on radiological findings and disease pathology.ResultsThe majority of patients (83%) had squamosal COM, while 17% had mucosal COM. Incus erosion was most common (60%), followed by stapes superstructure erosion (21%). Malleus was relatively resistant to erosion (15%). Ossicular chain discontinuity was observed in 60% of cases. In squamosal COM, varying degrees of ossicular chain damage were seen, with only 15% of cases having an intact chain.ConclusionHRCT temporal bone is a valuable tool for preoperative assessment of ossicular chain status in COM patients. Squamosal COM is associated with a higher incidence of ossicular erosion, particularly incus and stapes. HRCT scans help plan surgical interventions and improve outcomes.